การพัฒนาระบบประกันคุณภาพสำหรับกระบวนการผลิตรายการวิทยุ : กรณีศึกษา สถานีวิทยุแห่งจุฬาลงกรณ์มหาวิทยาลัย - ธนะรัฐ สุวะโจ (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
This research has for the purpose of developing the proper quality assurance system for the sample radio broadcasting station. The developed system intended to decrease the number of failures that occurred in radio processing. Besides supporting the quality system IS09002 development. From analyzing of factors that have effects with quality assurance process by cause and effect diagram. Therefore, were knowing the important effects, so when studying and improving of these factors, it would lead the way to quality assurance development. These factors to be composed of organization revising, supplied product control, material-product storage system, efficiency measurement, material–product inspection, non-conforming product control, tractability system, inspection equipment calibration, maintenance internal audit, customer complaint management and preventive action. When the factor had already been improved, the complete system was created by linking there function relationship. In the experiment, the system can decrease the number of failures together with supporting the procedures of customer complaint management, in addition can be taken to the one of quality system development which following the quality system standart of IS09002.